Being a hospice volunteer influenced medical students' comfort with dying and death - Khalaf, Roy (2012)
Being comfortable with death and communicating with patients near the end of life are important attributes in palliative care. We developed a hospice volunteer program to teach these attitudes and skills to preclinical medical students. Using a mixed-methods approach, validated surveys measured participants' and non-participants fear of death and communication apprehension regarding dying. Journals and focus groups examined participants' subjective experiences as their patient relationships evolved. Survey scores were significantly lower for participant hospice volunteers, indicating lower levels of death anxiety and communication apprehension regarding dying. An explanatory framework, using journals and focus groups, captured participants' sense of development over time into three categories: challenges, learning, and growth. This pilot project provides insight into the medical students' experiential learning as they participate in our hospice volunteer program.